Global Market of Chemical Crop Protection Agents: Forecasting Yield Losses and Economic Prospects for Domestic Pesticide Production - Alexander I. Tareev; Alexey V. Bereznov; Valery V. Smirnov; Anna A. Tareeva; Sofya S. Kislaya (Техника и технология пищевых производств)
To ensure its food security and economic growth, Russia needs to monitor the global pesticide market because constant monitoring predicts supply stability and provides annual high yields. The article describes the current issues associated with agricultural pesticide, analyzes the development directions on the global pesticide market, and predicts its impact on the Russian economy. To analyze the global market of chemical plant protection products, the authors applied an integrated approach based on analysis, synthesis, analogy, comparison, and forecasting. The research relied on the domestic laws and standards issued by the Ministry of Agriculture and the Federal Service for Veterinary and Phytosanitary Surveillance. Other sources included statistics obtained from foreign agencies (Phillips McDougal; Kynetec; NBS, China; Chemexcil, India) and Russian institutions (Rosstat, BusinesStat, Zerno.ru, etc.). The review included articles published in scientific and analytical databases, i.e., eLIBRARY.RU, AgroXXI, and AgroPages in 2018–2024. The analysis concentrated on India, China, and the Russian Federation. It covered absolute and relative harvest losses, as well as the market share of importing countries and key suppliers on Russian pesticide market. The demand for chemical pesticides continues to grow, despite restrictions or prohibitions of some hazardous pesticides. Some active ingredients were partially unavailable while finished formulations were subjected to import quotas. In 2024, Russia will be using as many chemical plant protection products as in 2023 since the domestic warehouses store large reserves. The weather conditions are likely to ensure optimal plant growth. Russian farmers will harvest about 142 million tons of grain, including 92–95 million tons of wheat. If repeated annually, this research may reduce the risk of harvest losses and allow the state to adopt prompt regulation measures to obtain high-quality products, thus increasing the domestic consumption and export potential.